THE PHENOL HYDROXYLATION USING A MoO3/TS-1 CATALYST THAT CALCINED ON THE VARIOUS TEMPERATURE - Anis Farika; Syafsir Akhlus; Didik Prasetyoko (Institut Teknologi Bandung, 2010)
MoO3/TS-1 catalyst has been proven have a higher catalityc activity rather than TS-1 on phenol hydroxylation reaction become a hydroquinone. Preparation catalyst using a impregnasi technique with ammonium molbidate as a precursor. Catalyst calcined at temperature 400-800°C and characterized by X-Ray Diffraction (XRD), pyridin adsorption, and hydrophilicity test. Calcinations temperature affects a catalyst characteristic and related to catalyst activity. MoO3/TS-1 catalyst has been calcined at temperature 400°C showed a higher hydrophilicity rather than TS-1, a faster speed reaction on phenol hydroxylation, and increasing of catalyst activity rather than initial catalyst, TS-1.